2016
DOI: 10.4102/sajbm.v47i3.66
|View full text |Cite
|
Sign up to set email alerts
|

Work locus of control and sense of coherence as antecedents of job insecurity

Abstract: Previous research has highlighted various antecedents of job insecurity, both in cross-sectional research and in a recent meta-analysis. A review of this literature indicates that work locus of control actually is the only personality antecedent that has received considerable attention, while sense of coherence may also be an important factor to consider. Data on biographical variables, cognitive and affective job insecurity, work locus of control and sense of coherence were gathered from employees across 3 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
2
0
1
Order By: Relevance
“…The perceived risk of COVID-19 will cause hospitality employees to worry about the uncertain prospects for their industry and own positions, leading to job insecurity. Consistent with previous research [ 63 , 64 ], job insecurity will lead to increased emotional exhaustion as employees fear the threat of resource loss. The COVID-19 pandemic has caused an economic downturn and high unemployment around the world.…”
Section: Discussionsupporting
confidence: 87%
“…The perceived risk of COVID-19 will cause hospitality employees to worry about the uncertain prospects for their industry and own positions, leading to job insecurity. Consistent with previous research [ 63 , 64 ], job insecurity will lead to increased emotional exhaustion as employees fear the threat of resource loss. The COVID-19 pandemic has caused an economic downturn and high unemployment around the world.…”
Section: Discussionsupporting
confidence: 87%
“…Um estudo desenvolvido por Hunter (2002) encontrou que pilotos com menor LOC interno apresentaram maior tendência a experimentar eventos mais perigosos relacionados à aviação, em comparação a pilotos com LOC interno dominante. Outro estudo sugeriu, de forma complementar, que uma orientação de LOC mais externa está relacionada com a falta de cautela, e à insegurança no trabalho (Pienaar & De Witte, 2016), o que pode resultar em falhas ao tomar medidas de precaução para evitar a ocorrência de desfechos desfavoráveis. Dessa forma, indivíduos com alta conscienciosidade -que mantém maior grau de cautela e controle para atingir e lutar por seus objetivos -apresentariam também maior LOC interno.…”
Section: Discussionunclassified
“…The present research made a significant contribution to such previous literature by firstly revealing that the perceived unstable work environment and the lack of personal control sense may be inducing factors that reduce the professional identity level of private kindergarten teachers in China-Mainland. According to the propositions of the Job-Demands-Resources Model, the perceived unstable work environment can be regarded as a special kind of pressure and turnover in essence is a negative strategy responding to the pressure (Bakker and Demerouti, 2007;Pienaara and Witte, 2016). Under this vein, increasing social supports from family/organization may be an effective way to alleviate the possible negative downstream effects of occupation stereotypes, because prior research has demonstrated that social supports can help employees cope with job stress effectively (Lambert et al, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 99%